Verifying Human Unique Identities using Fingerprint Reconstruction and Knuckle Reorganization - Kalpesh, Kumavat; Samiksha, Jadhav; Gauri, Burkul; Gaurav, Mahajan (International Journal of Computer Sciences and Engineering, 2025)
In this paper we proposed that, the set of minutia factors is taken into consideration to be the maximum different feature for fingerprint illustration and is extensively used in fingerprint matching. It turned into believed that the minutia set does now not contain sufficient data to reconstruct the unique fingerprint photograph from which minutiae had been extracted. The prior know-how approximately fingerprint ridge systems is encoded in terms of orientation patch and non-stop segment patch dictionaries to improve the fingerprint reconstruction. We additionally proposed a brand new or first publicly to be had database for minor (additionally foremost) finger knuckle photographs from 503 exceptional topics. The efforts to expand an automatic minor finger knuckle sample matching scheme reap promising outcomes and illustrate its simultaneous use to seriously enhance the overall performance over the conventional finger knuckle identification.